Engaging with (vs. avoiding) personalized advertising on social media - Loureiro, S. M. C.; Hollebeek, L.; Raouf, A. R.; Ruivo, L.; Kaljund, K.; Guerreiro, J. (Journal of Marketing Communications, 2025)
This study investigates binomial consumer brand engagement (vs. advertising avoidance) in the social media context. Grounded in social exchange theory, the relationships between personalized advertising, information control, privacy concerns, advertising avoidance, and consumer brand engagement are analyzed by drawing on a survey comprising n = 429 participants. The findings reveal that personalized advertising boosts brand engagement while also reducing privacy concerns. Additionally, it has been discovered that privacy concerns do not have a significant impact on consumers’ engagement with a brand. Overall, this study demonstrates that consumers can recognize personalized advertising and are open to relying on it.